2016
DOI: 10.1007/s00190-016-0920-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and assessment of triple-frequency BDS precise point positioning

Abstract: The latest generation of GNSS satellites such as GPS BLOCK-IIF, Galileo and BDS are transmitting signals on three or more frequencies, thus having more choices in practice. At the same time, new challenges arise for integrating the new signals. This paper contributes to the modeling and assessment of triple-frequency PPP with BDS data. First, three triple-frequency PPP models are developed. The observation model and stochastic model are designed and extended to accommodate the third frequency. In particular, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 21 publications
3
53
0
Order By: Relevance
“…In addition, some initial results are presented, including the analysis of cross-correlation and prediction for real-time precise positioning users as well as the IFCB of BDS-3 satellites. Guo et al [5] implemented the triple-frequency PPP with BDS data for the first time. However, the additional frequency had a marginal effect on the positioning accuracy in their results, likely because they neglected the effects of IFCB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some initial results are presented, including the analysis of cross-correlation and prediction for real-time precise positioning users as well as the IFCB of BDS-3 satellites. Guo et al [5] implemented the triple-frequency PPP with BDS data for the first time. However, the additional frequency had a marginal effect on the positioning accuracy in their results, likely because they neglected the effects of IFCB.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 3 has revealed that the third-frequency pseudorange has limited impact on float PPP solutions in terms of positioning errors and convergence times; this is because the addition of L5/B3/E5b signals does not improve the satellite geometry or the pseudorange precision, which are both critical to speeding up PPP covergence (see also Guo et al, 2016;Guo and Geng, 2018). Thus we show in the left panels of Fig.…”
Section: Multi-gnss Fcbsmentioning
confidence: 99%
“…As another alternative to traditional PPP which uses the ionosphere-free combination model, undifferenced and uncombined PPP has attracted a lot of attention in the GNSS field [25][26][27]. This solution is more flexible in processing multi-frequency GNSS observations, avoids noise amplification caused by traditional linear combination, and can extract ionospheric delays [28][29][30].…”
Section: Dual-frequency Multi-gnss Pppmentioning
confidence: 99%